Preferensi Konsumen terhadap Minuman Fungsional Berbasis Ekstrak Kumis Kucing (Orthosiphon aristatus) sebagai Jamu - Christofora Hanny Wijaya; Cindy Carolina (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
The development of Java tea extract-based functional drink as a new concept of jamu (Indonesian Traditional Herbal) drink has been carried out since 2006. However, there was no available consumer preference information, hence this study was conducted. This research aimed to identify the factors that influence consumer preferences on purchasing jamu specifically on the intensity of sensory attributes of ideal jamu. This allow pursuing the final target to determine the consumer acceptance towards concentrate Java tea extract-based functional drink. A chi-square analysis was performed to determine the relationship between the respondent’s demographic factors and consumer preferences for jamu. The demographic factors showed a significant association with consumer preferences for jamu at a significance level of 5%, except education. Aroma of spices was most preferable attribute for jamu, followed by sweetness, sourness and astringent attributes. Ethnicity, occupation, budget allocation for purchasing jamu per month influenced the preferable sensory attribute. The intensity of the sensory attributes of concentrated Java tea extract-based functional drinks was significantly incompatible to an ideal jamu drink, according to Wilcoxon test results. This result showed that consumers did not consider the developed concentrate having jamu criteria. The intensity of sweetness and astringency that met the consumer preference, orange aroma, and freshness attribute at high intensity, plus the unpleasant sensory characteristics of jam which could not be detected in the product might provide the product’s strengths that make the developed product potentially acceptable by market.